Simulation of cyber physical systems behaviour using timed plant models - Canadas, Nuno (2018)
When developing a reliable controller for cyber-physical systems, one of the main issues is to guarantee that all behaviour properties of such systems will be accomplished. For this purpose, it is very important to find and use formalisms and tools in order to model the controller and the respective plant. Moreover, it is very important to consider the same formalism for modelling both. The accurate model of a plant is usually difficult to obtain. To solve this problem, several techniques for modelling the plant have been developed in the recent past years. However, some of them have lacks that do not allow a fast, reliable and flexible way for plant modelling. In this paper a systematic approach for modelling cyber physical systems using timed automata is presented. The proposed approach allows defining a systematic way for creating global models for both the plant and the controller. These models, may be used to simulate and validate the cyber physical systems. For this purpose software tools, as UPPAAL, and other simulation configurations, as Model-in-the-loop and Hardware-in-the-loop, can be used. In order to present and explain the proposed methodology, a virtual platform and a physical workbench have been developed, from a transport objects station example, where Model-in-the-loop and Hardware-in-the-loop configurations are used in a subsequent manner in the context of the presented system modelling methodology.